From Spiritual Stations to Social Ethics: Reframing Sufi Maqāmāt as a Framework for Gender Justice - In'amuzzahidin , Muh.; Kharomen, Agus Imam; Hanik Rosyida; Fejrian Yazdajird Iwanebel (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2025)
This article reexamines the Sufi doctrine of maqāmāt (spiritual stations) as an ethical framework for articulating gender justice within Islamic thought. While classical Sufi literature—most notably al-Qushayrī’s al-Risālah—presents the maqāmāt primarily as a stage of spiritual discipline guiding the seeker toward proximity to God, their broader ethical implications for social relations remain underexplored. The central academic problem this study addresses is the persistent separation between Islamic spirituality and contemporary debates on gender justice, which are often framed solely in legal or socio-political terms. Through a qualitative, library-based analysis of classical Sufi texts, especially al-Risālah and related writings of al-Qushayrī, this article reconstructs the moral psychology of the maqāmāt as a virtue ethical framework grounded in ontological equality and moral accountability before God. The study argues that stations such as tawbah, zuhd, tawakkul, and riḍā cultivate ethical dispositions that challenge patriarchal assumptions and reorient social relations toward justice and reciprocity. By demonstrating that gender equity is a logical implication of Sufi spiritual anthropology, the article offers a new interpretive model linking Islamic spirituality to contemporary ethical discourse on gender justice.